Personal savings and household investments: a cohort study among primary school teachers - Emmanuel Akeny; David Mwesigwa (Annals of Management and Organization Research)
Purpose: This study aimed to determine the relationship between personal savings and household investments among a cohort of primary school teachers in lira city. Research methodology: The study used a cross-sectional survey design with a quantitative research approach. Data were collected from a sample of 103 respondents with the period between October 2020 and January 2021 using self-administered questionnaires. The Content Validity Index was used to establish validity, while the Cronbach's Alpha Coefficient was used to test reliability. Results: Using descriptive and inferential statistics, the results suggest that civil servants' personal financial planning is high due to personal savings. Also, the level of household investment is high and the correlation reveals that the relationship between private savings and household investment is very weak and negative. Limitations: This study focused on personal savings only, yet other constructs affect household investments. Contribution: This study's results help civil servants in Lira city and Uganda in general since personal savings are an essential factor to household investments. Keywords: Personal savings, Household investment, Primary teacher, Financial planning, Lira